Teaching Speaking Through Story Telling: South Sulawesi Folktales and Its Influence to the Students Speaking Competence - Abd Kadir Hakim; Bahrun Amin; Erwin Akib (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
In the world of globalization, communication plays a vital role in getting success in all fields. Language is used as a tool for communication, The objective of the research is certainly intend to answer and solve the problem statement which has been stated before and it’s the aim of this thesis. In line with the research question stated above, the objectives of this research are (1) To figure out the extend using South Sulawesi folktales by storytelling method can improve students speaking competence. (2)To find out the students responses towards using the South Sulawesi folktales by storytelling method in teaching speaking. In doing this study, quasi experimental research is used which requires the careful collection, analysis, and interpretation of quantitative data. based on the data analysis it can be concluded that the result of pretest and posttest scores of experimental class and control class, we could see that the posttest score was higher than pretest.